The effects of small-sided soccer games on tactical behavior and collective dynamics: A systematic review. (May 2020) - Clemente, Filipe Manuel; Afonso, José; Castillo, Daniel; Arcos, Asier Los; Silva, Ana Filipa; Sarmento, Hugo
Highlights: Smaller formats likely lead to increases in the tactical behaviors associated with penetration and defensive delays. Larger formats lead to an increase in the frequency of collective behaviors associated with attacking and defensive unity. Larger pitches are associated with a greater variability of movements during SSGs. Older players tend to explore the width of the pitch more and disperse themselves more than younger players during SSGs. Abstract: The present systematic review aims to describe evidence about the effects of different small-sided soccer games (SSGs) on tactical behaviors and collective dynamics. This study presents a systematic review, organizes the acute effects of the most common task conditions, and describes the common methodologies used in previous studies. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, this systematic review searched for studies on Web of Science, PubMed, and SPORTDiscus. The search returned 95 papers. After screening the records against set criteria, 34 articles were fully reviewed. The main topics related to tactical behaviors and collective dynamics were (1) the effects of different formats; (2) the effects of different pitch sizes and configurations; (3) the effects of tasks adjustments; (4) the effects of age and competitive and expertise levels; and (5) multidimensional effects. In summary, and among other evidence, this systematic review revealed that smaller formats likely lead to increases in the tactical behaviors associated with penetration and defensive delays, while larger formats may lead to an increase in the frequency of collective behaviors associated with attacking and defensive unity. Moreover, using floaters may increases the effective playing space, and considerable numerical imbalances contribute to a possible more stable defensive dynamic. Finally, the few studies that tested such a hypothesis revealed greater variability of movements in larger pitches comparing to smaller ones.